Atenolol, sustained-release oxprenolol, and long-acting propranolol in hypertension. Issue 6231 (28th June 1980) - Petrie, J C; Jeffers, T A; Robb, O J; Scott, A K; Webster, J
Abstract : The effect of once-daily atenolol, sustained-release oxprenolol (a new formulation of oxprenolol presented as a compressed tablet in a waxed matrix), and long-acting propranolol (a new formulation presented as spheriods in a capsule) was studied in a double-blind crossover trial in 23 carefully selected hypertensive outpatients. After a run-in period with matching placebo each patient received atenolol (100 mg/day), sustained-release oxprenolol (160 mg/day), long-acting propranolol (160 mg/day), and placebo according to a randomised sequence. After four weeks' treatment with sustained-release oxprenolol blood pressure in the two to four hours before the next dose was not significantly lower than after placebo. The effectiveness of atenolol and of the new formulation of propranolol in reducing blood pressure was confirmed. These results suggest that the present formulation of sustained-release oxprenolol should be reconsidered.